Notfallversorgung und Erstbehandlung epileptischer Anfälle im Erwachsenenalter - Schiefer, Johannes; Surges, Rainer (DMW - Deutsche Medizinische Wochenschrift, 2019)
Suspected epileptic seizures are a frequent cause of emergency hospital care. After single seizures, the emergency management includes safety measures and diagnostic efforts to distinguish epileptic seizures from its manifold mimics and to possibly detect acute causes of epileptic seizures. Convulsive status epilepticus requires rapid anticonvulsant treatment according to established protocols and diagnostics to rule out underlying acute brain diseases. After a first seizure, typical EEG- and MRI findings may indicate an elevated recurrence risk, thereby justifying the ultimate diagnosis of epilepsy and initiation of anticonvulsant therapy. This article reviews the recent definition of epilepsy, summarizes clinical characteristics of epileptic seizures and its mimics and provides an overview of established therapies of single convulsive seizures, convulsive status epilepticus and early care of adults after first unprovoked seizures.
Keywords: Status epilepticus; erster epileptischer Anfall; Notfallmanagement; Erstversorgung; Antikonvulsiva